âTidak Menang Tampang Doangâ: Kombinasi Outer dan Inner Beauty di Kalangan Mahasiswi - Purnama Sari, Andi Tri (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
How women interpret their own body is associated with their social environment since beauty indicators is unique. This article deals with how female student perceive beauty and how this is related to their academic life. To be beautiful is something that is coveted and sought by almost all women, including college female students. For them, campus is not only a place for studying, but also a place for displaying beauty. Beauty is important for female students because it significantly affects oneâs self-confidence and provides various advantages, particularly related to administrative and academic affairs. Beauty that is coveted by female students is a combination between outer and inner beauty. While the former is associated with âprettinessâ (keindahan) of physical appearance (hair, face, body shape and body skin), the latter is related to âattractivenessâ (kemenarikan) of non-physical appearance (intellectual quotient and personality). In the context of academic capability, female students who rely on beauty, but are not smart are considered as students who are âmenang tampang doangâ, not to mention when they havenât had both. In addition, female students who are not smart, but has good personality will look beautiful. However, those who have the combination of beauty and intelligence are seen as âmahasiswi plus-plusâ and are regarded as students who are âtidak menang tampang doangâ. This underlines the complementarity between inner and outer beauty.